PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), DAN TOTAL ASSET TURNOVER (TATO) TERHADAP RETURN ON ASSET (ROA) PADA SUB SEKTOR FOOD AND BEVERAGE PERIODE 2018-2023 - Anis Stasya; Nurismalatri (Journal of Research and Publication Innovation, 2025)
This research aims to examine the influence of Current Ratio (CR), Debt to Equity Ratio (DER), Total Assets Turnover (TATO) on Return on Assets (ROA) in food and beverage companies listed on the Indonesia Stock Exchange. This type of research uses a quantitative approach. The number of samples used in this research was 6 food and beverage companies, namely PT. Aksha Wira Internasional Tbk. (ADES), PT. Sariguna Primatirta Tbk. (CLEO), PT. Ultrajaya Milk Industry Tbk. (ULTJ), PT Campina Ice Cream Industry Tbk. (CAMP), PT. Siantar Top Tbk. (STTP), PT. Indofood cbp is successful and prosperous Tbk. (ICBP) during the 2018-2023 observation period. This research uses secondary data obtained from annual financial reports. The analytical method used is Panel Data regression analysis of the EViews (Econometrics Views) program version 13. The research results show that the Current Ratio (CR) has no effect on Return on Assets (ROA) as indicated by the t-count value of 0.651689 and a significance of 0. 5201 > 0.05, Debt to Equity Ratio (DER) has a significant negative effect on Return on Assets (ROA) with a t-value of -2.444330 and a significance of 0.0213 < 0.05, and Total Assets Turnover (TATO) does not has an effect on Return on Assets (ROA) with a t-value of -0.500148 and a significance of 0.6210 > 0.05. Simultaneously, Current Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) have a significant effect on Return on Assets (ROA) with an f-count value of 4.882154 and a probability value of 0.000839 < 0, 05 in food and beverage companies listed on the Indonesia Stock Exchange in the 2018-2023 period.